2020
DOI: 10.1038/s41398-020-00950-y
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of mental health problems among patients with cancer during COVID-19 pandemic

Abstract: The current study aimed to explore mental health problems in patients diagnosed with cancer during the COVID-19 pandemic. A cluster sampling, cross-sectional survey with 6213 cancer patients was conducted in one of the largest cancer centers in China. The socio-demographic and clinical characteristics, psychosomatic conditions, interpersonal relationships and social support, COVID-19 infection-related psychological stress, and mental health status were measured. Medical conditions were extracted from patients’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
243
5
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(298 citation statements)
references
References 43 publications
14
243
5
7
Order By: Relevance
“…In addition, while the impacts of COVID-19 visitation policies and their consequences have been examined in the context of intensive care unit (ICU) care of COVID-19 patients, 31 , 32 RUD patients’ complex health challenges require increased advocacy even when accessing routine care. On the other hand, the limited literature in other patient groups indicates that those grappling with complex health conditions, such as cancer, 33 during the pandemic also are at risk for serious mental health challenges, such as those described by our respondents. Our qualitative data further suggest that the anxiety caused by the pandemic may be leading some RUD patients to forgo treatment altogether, with potentially catastrophic implications for their already complex health.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, while the impacts of COVID-19 visitation policies and their consequences have been examined in the context of intensive care unit (ICU) care of COVID-19 patients, 31 , 32 RUD patients’ complex health challenges require increased advocacy even when accessing routine care. On the other hand, the limited literature in other patient groups indicates that those grappling with complex health conditions, such as cancer, 33 during the pandemic also are at risk for serious mental health challenges, such as those described by our respondents. Our qualitative data further suggest that the anxiety caused by the pandemic may be leading some RUD patients to forgo treatment altogether, with potentially catastrophic implications for their already complex health.…”
Section: Discussionmentioning
confidence: 82%
“…Nonetheless, the use of specific factors seems to be useful to address specific questions in both clinical and research. For example, in recent studies concerning mental health related to the pandemics, Wang et al, 36 and Ellis et al, 37 used hostility and depression subscales to address specific questions related to psychological distress in cancer patients and adolescents in isolation, respectively. Thus, our results support a similar score interpretation approach to address specific issues in mental health for the Brazilian BSI version.…”
Section: Discussionmentioning
confidence: 99%
“…The widespread contagion and lockdown of the COVID-19 have caused considerable mental health problems such as anxiety, depression, and post-traumatic stress symptoms (Castelli et al, 2020;Talevi et al, 2020;Torales et al, 2020;Vindegaard and Benros, 2020). Different levels of psychological distress may appear depending on the healthcare workers (Di Tella et al, 2020;Lai et al, 2020;Li et al, 2020;Vindegaard and Benros, 2020), the elderly (Yang et al, 2020), and the presence of underlying disease (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In a recently published study of the cancer patients in China during the COVID-19 pandemic, patients reported adverse psychiatric symptoms with the highest percentages accounted for by depression, anxiety, and PTSD which were 23.4, 17.7, and 9.3%, respectively (Wang et al, 2020). Even in normal times, fear and anxiety affect the course of underlying diseases (Vanni et al, 2020).…”
Section: Introductionmentioning
confidence: 99%